Gene Expression Comparison Between the Injured Tubercule Skin of Turbot (Scophthalmus maximus) and the Scale Skin of Brill (Scophthalmus rhombus) - Estêvão, João (2024)
Turbot and brill are two congeneric commercial flatfish species with striking differences in skin organization. The calcified appendages in turbot skin are conical tubercles, while in brill, they are elasmoid scales. A skin injury involving epidermal and dermal levels was evaluated 72 h post-injury to compare the skin regeneration processes between both species. An immune-enriched 4x44k turbot oligo-microarray was used to characterize the skin transcriptome and gene expression profiles in both species. RNA-seq was also performed on the brill samples to improve transcriptome characterization and validate the microarray results. A total of 15,854 and 12,447 expressed genes were identified, respectively, in the turbot and brill skin (10,101 shared) using the oligo-microarray (11,953 and 9629 annotated). RNA-seq enabled the identification of 11,838 genes in brill skin (11,339 annotated). Functional annotation of skin transcriptomes was similar in both species, but in turbot, it was enriched on mechanisms related to maintenance of epithelial structure, mannosidase activity, phospholipid binding, and cell membranes, while in brill, it was enriched on biological and gene regulation mechanisms, tissue development, and transferase and catalytic activities. The number of DEGs identified after skin damage in brill and turbot was 439 and 143, respectively (only 14 shared). Functions related to catabolic and metabolic processes, visual and sensorial perception, response to wounding, and wound healing were enriched in turbot DEGs, while metabolism, immune response, oxidative stress, phospholipid binding, and response to stimulus were enriched in brill. The results indicate that differences may be related to the stage of wound repair due to their different skin architecture. This work provides a foundation for future studies directed at skin defense mechanisms, with practical implications in flatfish aquaculture.